Microstructure profile on selected-traditional Indonesian herbal powder - Naqiyah A. Mulachelah; Syahputra Wibowo; Sri Widyarti; Sutiman B. Sumitro (The East Java Biological Society, 2022)
Jamu is well known as traditional herbal medicine that has been used by Indonesian for centuries ago. Local people usually consume jamu for maintaining health and therapy diseases because it is cheaper and has less side effects. Scientific approach needs to be done to study the characteristic of the herbals. This research aims to characterize Indonesian herbal medicine based on microstructure using Scanning Electron Microscope (SEM). The samples for this research are rosela flower (Hibiscus sabdariffa), ginger (Zingiber officinale), lime fruit (Citrus aurantifolia), and celebes pepper (Piper crocatum). The infusion method preparation was carried out. The mixture was processed further by a freeze-drying method to obtain a powder form. SEM was utilized to capture the herbal powder image. Size of distribution and surface roughness were analysed by ImageJ and Origin Pro 8 on SEM images. The size measurement result showed that infused Rosella has the biggest grain (53.5 µm), followed by lime (43.8 µm), ginger (41.2 µm) and celebes pepper (38.4 µm). The surface roughness results showed that the roughest samples of all is ginger (Ra = 64.417), followed by lime (Ra = 58.761), celebes pepper (Ra = 43.589), and rosella (Ra = 30.855). In conclusion, based on its size measurement result, celebes pepper is the most soluble and has the highest bioavailability, followed by ginger, lime, and rosella. According to its surface roughness, celebes pepper also showed the most soluble compared to other samples, followed by lime, ginger and rosella.